Tea for two: bringing informal communication to repositories - Baptista, Ana Alice (2007)
Although informal communication has always been a part of scholarly communication, its value as an important means for sharing perceptions and knowledge has not always been recognized or properly put to good use. Three add-ons for the DSpace platform have been developed under the "DSpace Dev@University of Minho" project. The next natural step is to further develop and integrate the features of these add-ons into a new cross-repository service that allows knowledge to be transferred across communities in a broader and improved way and to provide better means to access comprehensive information about communication relationships between scholarly entities. Some of the changes that will have to be made to the current features of these add-ons in order to implement such a system have been identified and described in this article. We also present the rationale that supports the vision of a system that accommodates the add-ons developed. Such a system will provide an informal communication layer at the top of the existing network of repositories directly connected to the formal one. In addition, some changes are proposed to the way the Web of Communication is calculated and depicted in order to provide more qualitative information about the communication relationships between scholars.